The Art of Working in Hair: Hair Jewellery and Ornamental Handiwork in Victorian Britain. (4th May 2019) - Yan, Shu-chuan
Abstract: This article explores the meanings of hair jewellery in Victorian Britain as a bodily fragment that could be braided or woven into an artifact of affection, a material for memory, and most vital of all, a popular ornamental object of fashionable consumption. Special attention will be paid to how the wearing and making of hair jewellery among women became a widespread fad as represented in manuals, pattern books, and periodical literature. These publications facilitate an investigation of the performance of female identity and self-display in connection with the culture and tradition of handicrafts. They reveal an important aspect of Victorian ladies' modes of possession, as shown in their use of hair artifacts as decorative items to adorn their bodies. I argue that practices of fancy hair-work were productive and creative within the ideology of domesticity, equipping women for modern living and marking their engagement with commodity culture, including professional hair-work services. The art of working in hair plays a crucial role in the making of tangible and sensory memories objectified and personalized in everyday lives.